Development of students' social interaction in virtual environments - Lee, Jia Wing (2023)
Virtual reality (VR) technology is the perfect communication tools, which is on the cutting edge of the general evolution of the current communication interface. VR offers user a fully immersive environment and can simulate vivid communication and a social experience that is almost exactly like the real thing. In recent years, VR technologies have mainly been used for leisure activities like gaming and watching videos, or for more traditional uses like meetings or in some professional fields, like medicine, engineering. There are only a small number of VR environments or systems specifically designed for students that allow them to interact socially with others in the virtual environment. Social distance has been established in the midst of the COVID-19 pandemic, which forbids any face-to-face social interactions between people. The shift to a virtual mode of study limited social contact, and students can only use social media platform to interact with each other, which is a poor substitute for more traditional forms of communication. This project aims to create a VR environment where students can be socially active among peers and eliminates the condition of going outdoor to perform face to face interaction.